A natural quercetin-based fluorescent sensor for highly sensitive and selective detection of copper ions1. Issue 11 (7th June 2015) - Yang, Shilong; Yin, Bin; Xu, Li; Gao, Buhong; Sun, Haijun; Du, Liting; Tang, Ying; Jiang, Weina; Cao, Fuliang
<x xml:space="preserve">Abstract</x> A natural quercetin-based fluorescent sensor for highly sensitive and selective detection of copper ions has been studied.